Anticompetitive Vertical Integration by a Dominant Firm - Riordan, Michael H. (American Economic Review, 1998)
Backward vertical integration by a dominant firm into an upstream competitive industry causes both input and output prices to rise. The dominant firm's cost advantage may or may not offset the negative effect of higher prices on social welfare. Whether it does depends on a simple indicator derived from input and output market shares and the degree of piror vertical integration. A vertical merger is similar to a hypothetical horizontal merger, suggesting that vertical merger policy for this industry should be similar to horizontal merger policy. The dominant firm model yields an observable sufficient indicator of welfare-improving vertical mergers.